Pengaruh model pembelajaran everyone is a teacher here terhadap keterampilan berbicara peserta didik kelas VIII di SMP IT Samawa Cendekia - Kurniawati, Luthfiyah (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2024)
This research aims to determine the effect of implementing the everyone is a teacher here (ETH) learning model on the speaking skills of class VIII students at SMP IT Samawa Scholar. The type of research used in this research is quantitative research with a quasi-experimental approach and the research design used by researchers is posttest only control design. In this design, there are two groups selected at random, and then given a posttest to find out whether there are differences between the experimental group and the control group in the final situation. Based on the test results obtained and the results of the analysis that has been carried out, it can be concluded that the use of the everyone is teacher here learning model has an influence on students’ speaking skills in class VIII Indonesian language subjects at SMP IT Samawa Scholar. Abstrak Penelitian ini bertujuan Untuk mengetahui pengaruh penerapan model pembelajaran everyone is a teacher here (ETH) terhadap keterampilan berbicara peserta didik kelas VIII di SMP IT Samawa Cendekia. Jenis penelitian yang digunakan dalam penelitian ini adalah penelitian kuantitatif dengan pendekatan quasy eksperiment dan desain penelitian yang digunakan oleh peneliti adalah post-test only control design. Dalam desain ini terdapat dua kelompok yang dipilih secara random, kemudian diberi post-test untuk mengetahui keadaan akhir adakah perbedaan antara kelompok eksperimen dan kelompok kontrol. Berdasarkan hasil tes yang diperoleh dan hasil analisis yang telah dilakukan, dapat disimpulkan bahwa penggunaan model pembelajaran everyone is teacher here memiliki pengaruh terhadap keterampilan berbicara peserta didik pada mata pelajaran bahasa Indonesia kelas VIII di SMP IT Samawa Cendekia.